The prevalence of diabetic retinopathy, risk factors, visual impairment and ocular status among patients with diabetes mellitus presenting to Berhan Aini National Referral Hospital, Eritrea: A hospital based study - Bastola, P; Kahsay, F; Zewengiel, S; Muguleta, M M (Journal of Chitwan Medical College, 2017)
Diabetic Retinopathy (DR) is the most common ocular complication in the diabetic population and the leading cause of blindness amongst working age group. There is a paucity of data about DR and various factors in Eritrea. The study aimed to find the prevalence of diabetic retinopathy, risk factors, visual impairment and ocular status among patients with diabetes mellitus in Asmara, Eritrea. This was a hospital based, Mixed method, descriptive study, all the consecutive patients attending the retina clinic of the hospital were enrolled in the study from January, 2014 to October, 2016. Early Treatment Diabetic Retinopathy Study (ETDRS) and Modified Airlie House classification were followed to evaluate the various stages of diabetic retinopathy and clinically significant macular edema (CSME). The guidelines developed by International Council of Ophthalmology (ICO) were followed to determine the need for interventions. Of the 506 diabetic subjects attending Berhan Aini National Referral Hospital; 435 (86.0%) subjects had type 2 Diabetes Mellitus (DM). 425 (84.0%) subjects had diabetic retinopathy. Moderate visual impairment, severe visual impairment and blindness due to diabetic retinopathy was observed in 139 (27.1%), 57 (11.1%), 76 (15%) subjects respectively while 234 subjects (46.2%) had normal vision. Hypertension 309 (61%) was the most common risk factor followed by duration of diabetes, occupation and the level of glycosylated Hemoglobin. 481 (95%) of the literate subjects were aware about diabetic retinopathy (P=<0.01). 277 (54.7%) subjects needed prompt treatment. There is a high prevalence of DR in patients attending Berhan Aini National Referral Hospital (BANRH). Awareness about diabetic retinopathy was good still the knowledge about primary prevention was not good enough.